Summary Record of Second Development Commissioners' Conference on Community Projects (16th April to 19th April 1953) - Planning Commission (Planning Commission, 1953)
Expansion Programme—National Extension Service and Community Development.—The expansion programme proposed to be undertaken during the Plan period would consist of 900 National Extension Service Development Blocks, which together with the 165 Community Project Development Blocks during 1953-54, would cover about one-fourth of the country. Out of these 900 development blocks, about 400 would be chosen for intensive development on the lines of Community Development Programme. Details of the programme as also its financial implications would be examined by the State Governments.
Community Projects Administration Planning Commission Government of India